Culture Shock Mahasiswa PMM 2 Asal Sumatera Utara di Pulau Jawa - Santa Goretty Pintubatu; Angela Anatasya Regina Bangun; Grance Luvita Sanaya Simanjuntak (Journal on Education, 2023)
Culture Shock is a cultural shock event experienced by someone when faced with a new environment. Culture Shock was also experienced by PMM 2 students who are domiciled in North Sumatra and made an exchange to Java Island. The purpose of this study was to find out the differences between the respondent's domiciled and the respondent's PMM location. The instrument used in this study was distributing questionnaires to respondents. The results of the study found that there were significant differences between the culture in the respondent's domiciled location and the respondent's PMM location